Pemanfaatan Citra Landsat 8 dan Google Earth untuk Identifikasi Lahan Sawah di Kecamatan Cibiru Kota Bandung - BUDY FRASETYA; YATI SETIATI; REZA SEPTIANUGRAHA; GHAZI MUHAMMAD (Program Studi Agroekoteknologi, Fakultas Pertanian, Universitas Udayana, 2018)
Utilization of Landsat 8 and Google Earth For Identification of Land in Cibiru Bandung CityThe availability of paddy field in urban areas from year to year experienced a decrease in wetland area as a result of conversion agricultural land to non-agricultural. Cibiru Sub Region City (SWK) Ujungberung is one of the priority areas of development. The goal of Bandung City government to have eternal paddy field needs to be supported with distribution of rice fields map for development and minimize land use conversion. The research method was used descriptive survey method, Landsat 8 and Google earth image interpretation results are then validated by conducting field surveys at the location points of the initial interpretation of rice fields and other land cover that is still verification from the results of studio intrepetation. The results obtained by NDVI value of Landsat 8 image for paddy field in Kecamatan Cibiru minimum 0.09296; maximum 0.23502 with an average of 0.16225. The result of identification with high resolution image google earth width of rice field in District of Cibiru identified 58.47 hectares.